การศึกษาการดำเนินงานการใช้หลักสูตรตามแนว โครงการบูรณาการคุณธรรม จริยธรรม ค่านิยมและคุณลักษณะอันพึงประสงค์ ในการสอนอาชีวศึกษาของสถานศึกษานำร่อง กรมอาชีวศึกษา - สุจิตรา โปร่งแสง (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
The objectives of this research are to study the operations and problems of a curriculum implementation by the Integration of Moral, Ethical, Norm and Desirable Characteristics Required in Vocational Education Teaching in Pilot Colleges. Data was provided by administrators and instructors from 22 Pilot College vocational education programs. The researcher collected this data through questionnaires, which was then analyzed and calculated in percentage. Results of this study showed that for preparation, the colleges would set additional policy for each institutions. They would set up an administrative board and study initial data. Administrative board meetings would then be held for project planning, announcement and instructor training. Problems that were encountered began with the colleges lacking necessary information to develop a system and faculty expertise. Instructors studied concerning the 14 traits, curriculum analysis, course natural traits analysis, selection of morals and ethics to be taught and course planning. They found they didn’t understand or have enough time to develop proper lesson plans. During operation, it was found the pilot colleges did promote and support the program as well as faculty development. They provided the necessary assistance, enhancing teachers’ convenience, improving teaching environments and improving overall administration for instructional management focus on child-centered. Supervision were also implemented to assist teachers. Special activities were also organized to instruct students in morals and ethics. Still, supervision were not regular and causing problems. Teachers had too much burden and the activities were not interesting so did not draw the attention of students. They said they had the opportunity to review teaching plans as well as project activities that include lectures, group work, on-the-job training and question-answer sessions. Teachers recorded student behavior on provided forms, which also included recording work results concerning moral and ethics, based on an 80:20 ratio. The problems they had were that there were too many students at every level and they lacked experience and expertise. An evaluation, colleges evaluated the necessary traits for students in each semester and combined the data before presenting them to administrators. Teachers, evaluated teaching plans and presented data in order to adjust and improve the plans. Problems they encountered were lack of planning in summaries and report, or reviews of the programs by the implementing pilot colleges and teachers not having sufficient time to improve the plans properly.